Dimers from α‐alkoxybenzyl radicals. An NMR study - Goh, S.H.; Ong, S.H.; Sieh, I. (Heyden & Son, 1971)
meso and dl Dimers (ArCHOR)2 where R is Me, Et, iPr, tBu, cyclohexyl and 1‐adamantyl may readily be differentiated by their NMR spectra; the benzylic protons of the meso isomer always absorb at a slightly higher field than those of the dl isomer in each of the solvents used. Differences in chemical shift are discussed in terms of preferences in conformer distribution. The formation of equal amounts of both dimers from the corresponding radical ArCHOR shows that steric and polar factors are not important in influencing the dimerization. Magnetic non‐equivalence due to the presence of asymmetric centres was found in some of the compounds discussed above. Copyright © 1971 Heyden & Son Ltd.